2021
DOI: 10.14336/ad.2020.0714-1
|View full text |Cite
|
Sign up to set email alerts
|

G. sinense and P. notoginseng Extracts Improve Healthspan of Aging Flies and Provide Protection in A Huntington Disease Model

Abstract: In the last decades, the strong increase in the proportion of older people worldwide, and the increased prevalence of age associated degenerative diseases, have put a stronger focus on aging biology. In spite of important progresses in our understanding of the aging process, an integrative view is still lacking and there is still need for efficient anti-aging interventions that could improve healthspan, reduce incidence of age-related disease and, eventually, increase the lifespan. Interestingly, some compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Ophiopogonis has been reported to stimulate lymphocyte proliferation in vitro [ 28 ]. Both are used for the benefit of qi and to promote body fluid production, according to TCM theory, and they are also reported to have the effects of cardiovascular protection, anti-inflammation and anti-cancer [ 27 , 29 , 30 ]. Although in vitro and in vivo studies have provided evidence supporting the purported effects of these ingredients of ZYLGS, we still perceive a need for a clinical trial to assess the efficacy of CHM formula in treating RT-induced OM.…”
Section: Discussionmentioning
confidence: 99%
“…Ophiopogonis has been reported to stimulate lymphocyte proliferation in vitro [ 28 ]. Both are used for the benefit of qi and to promote body fluid production, according to TCM theory, and they are also reported to have the effects of cardiovascular protection, anti-inflammation and anti-cancer [ 27 , 29 , 30 ]. Although in vitro and in vivo studies have provided evidence supporting the purported effects of these ingredients of ZYLGS, we still perceive a need for a clinical trial to assess the efficacy of CHM formula in treating RT-induced OM.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other species of the genus Ganoderma , G. sinense is used as herbal medicine and health supplement. It has been reported to have antitumor (Han et al, 2021 ), antiaging (Teseo et al, 2021 ), anti-inflammatory (Mei et al, 2019 ), and anticancer (Zheng et al, 2018 ) activities and nitric oxide inhibitory properties (Wang et al, 2020 ). Polysaccharides are the major biological components of G. sinense (Y. Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is especially suitable for patients with hypertension, hyperlipidemia, hyperglycemia, heart and cerebrovascular diseases, and patients who have low immunity, anemia, and are prone to falling and sprains ( Hawthorne et al., 2022 ; Jiang et al., 2022 ; Zheng et al., 2022 ). Additionally, it improves blood circulation, moisturizes the skin, and slows down aging ( Peng et al., 2017 ; Teseo et al., 2021 ). Phytochemical and pharmacological studies of P. notoginseng have demonstrated that its main biologically active components are dammarane-type saponins consisting of protopanaxadiol and protopanaxatriol glycosides ( Qiao et al., 2018 ; Marianela et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%